Perceptions of prevalence, consequences, and strategies for managing contraband substance use in an inpatient concurrent disorders program: A qualitative study of patient perspectives and survey of clinician perspectives - Rahman, Liah; Raymond, Holly; Labuguen, Bradley; Gladysz, Hollie; Holshausen, Katherine; Brasch, Jennifer; Amlung, Michael; MacKillop, James (Frontiers in Psychiatry, 2022)
Objective: Inpatient treatment programs for substance use disorders typically have an abstinence policy for patients, but unsanctioned substance use nonetheless takes place and can have significant negative clinical impacts. The current study sought to understand this problem from a patient perspective and to develop strategies for improved contraband substance management in an inpatient concurrent disorders sample. Methods: First, a qualitative study (n=10; 60% female) was undertaken to ascertain perceived prevalence, impact, and patient-generated strategies. Second, an anonymous follow-up survey was conduct with unit staff clinicians to evaluate the suggested strategies. Results: Patients reported the contraband substance use was present and had significant negative consequences clinically. Recommendations from patients included more extensive urine drug screening, the use of drug-sniffing dogs, and direct contingencies for contraband use. Nineteen staff competed an anonymous follow-up questionnaire to evaluate the viability of these strategies, revealing variable perceptions of feasibility and effectiveness. Conclusions: These findings emphasize the adverse consequences of contraband substance use in addiction treatment programs and identify patient-preferred strategies for managing this challenge.